IDENTIFICATION OF THE STRATA OF LATERITIC SOILS AND ALTERITES IN BENIN. - Gbaguidi, Victor S.; KIKI, Yvette Tankpinou; Zevounou, Crépin; Vedogbeton, Nestor; Zankpe, Marcel (My University, 2018)
This paper aims at exploring the sites of raw materials used in the production of laterite briquettes in Benin Republic. Specifically, the work was based on the investigation, delimitation and evaluation of the reserves of lateritic soils and alterites that may be included in the production of laterite briquettes. The tests showed thirty-three (33) favorable sites among which eighteen (18) lateritic soils and fifteen (15) alterites identified in the twelve Benin departments on the plateaux of the coastal sedimentary basin (lateritic soils) as well as on the crystalline bedrock, the Buem and the sedimentary basin (alterite) of Kandi. The various sections of wells obtained revealed a homogeneity on the sites of lateritic soils. Moreover, they appear as coherent soils while alterites present a more or less indurate appearance. The bedrock profiles varied between 1.2 and 2.2m comparatively to plateaux where the depths of the wells reached more than 5m. The established reserves are estimated to be 10 410 949m 3 for lateritic soils and 724 806 m 3 for alterites; which represents a great asset with regard to the high price of usual construction materials and the environmental challenge. Thus, local materials impose themselves day by day.
Keywords: lateritic soils; alterites; reserves .